A calcaneus attributable to the primitive late eocene anthropoid Proteopithecus sylviae: Phenetic affinities and phylogenetic implications. Issue 3 (22nd June 2013) - Gladman, Justin T.; Boyer, Doug M.; Simons, Elwyn L.; Seiffert, Erik R.
ABSTRACT A well‐preserved calcaneus referrable to Proteopithecus sylviae from the late Eocene Quarry L‐41 in the Fayum Depression, Egypt, provides new evidence relevant to this taxon's uncertain phylogenetic position. We assess morphological affinities of the new specimen using three‐dimensional geometric morphometric analyses with a comparative sample of primate calcanei representing major extinct and extant radiations (n = 58 genera, 106 specimens). Our analyses reveal that the calcaneal morphology of Proteopithecus is most similar to that of the younger Fayum parapithecid Apidium. Principal components analysis places Apidium and Proteopithecus in an intermediate position between primitive euprimates and crown anthropoids, based primarily on landmark configurations corresponding to moderate distal elongation, a more distal position of the peroneal tubercle, and a relatively "unflexed" calcaneal body. Proteopithecus and Apidium are similar to cercopithecoids and some omomyiforms in having an ectal facet that is more tightly curved, along with a larger degree of proximal calcaneal elongation, whereas other Fayum anthropoids, platyrrhines and adapiforms have a more open facet with less proximal elongation. The similarity to cercopithecoids is most plausibly interpreted as convergence given the less tightly curved ectal facets of stem catarrhines. The primary similarities between Proteopithecus and platyrrhines are mainly in the moderate distal elongation and the more distal position of the peroneal tubercle, both of which are not unique to these groups. Proteopithecus and Apidium exhibit derived anthropoid features, but also a suite of primitive retentions. The calcaneal morphology of Proteopithecus is consistent with our cladistic analysis, which places proteopithecids as a sister group of Parapithecoidea. Am J Phys Anthropol 151:372–397, 2013.© 2013 Wiley Periodicals, Inc.